Antithyroid Peroxidase and Thyroid Hormones in a Sample of Iraqi Patients with Type 2 Diabetic Mellitus - Fakri, Yasameen Ali; Al-Jowari, Suha Abdul-Khaliq (Iraqi Journal of Science, 2023)
This study aims to investigate the relationship between thyroid peroxidase antibody (TPO) and thyroid function tests (TSH, T3 and T4) in patients with type 2 diabetes mellitus (T2DM). Ninety women and men, with ages ranging between 35-65 years and weighing 60-80 kgs, were selected for this study. They were classified into three groups: G1 included 15 healthy control group, G2 had15 patients with T2DM and G3 had 60 patients with T2DM and hypothyroidism. Blood samples were collected from each individual via vein puncture to assess thyroid hormone and TPO-Ab. The results showed highly significant (p < 0.01) increase in TSH level in the diabetic group with hypothyroidism when compared to the other groups. There was no significant difference between diabetic and control groups. T4 and T3 levels showed highly significant (p<0.01) decrease in the diabetic group with hypothyroidism when compared to the diabetic and healthy control groups. On the other hand, there was no significant difference between the diabetic and healthy control groups. The results showed highly significant (p < 0.01) increase in the TPO-AB level in diabetic group with hypothyroidism when compared with the diabetic and healthy control groups.